Allá donde las piedras son el Tiempo - Riello Velásco, José María (Anales de Historia del Arte, 2006)
This article does not try to be more than a small preface to the catalogue that shows the presence of Rome in the old books that belonged to the Library Philology of Universidad Complutense and today keeps the Historic Library «Marqués de Valdecilla» (UCM). The two routes that operated the image of the city are reviewed: Mirabilia Urbis Romae and the scientific or pre-archeological studies. Finally the catalogue is suplemented with the books of this matter, today well preserved at the Historic Library.